Dejavniki likovne ustvarjalnosti in likovnopedagoško delo - Herzog, Jerneja (Revija za elementarno izobraževanje, 2009)
Factors in art creativity and art pedagogy work. This article presents the results of research done on the level of artistic creativity in primary school children and the gender-related differences among them. A study of the connections among factors of artistic creativity was also included in the research. The results of the present research indicate that there are no statistically significant differences between the genders in regard to the total values of factors that stimulate artistic creativity and the factors that enable artistic creativity. Results relating to the connections among individual factors indicate that there is a strong connection between complementary pairs of artistic creativity factors.